The Impact of Strategic Leadership on Crisis Management - Thani, Fahid Ben Hamed Al; Obeidat, Abdallah Mishael (International Journal of Asian Social Science, 2020)
The crisis is an unusual and stressful event. It is highlighted by the strategic gap due to the lack of adaptation to the changes that occur in the organization's environment. This study aims to identify the reality of strategic leadership represented by (investing strategic capabilities, defining strategic direction, improving and developing human capital, strengthening organizational culture with ethical practices, implementing balanced regulatory supervision) and crisis management represented by (detection of warning signals, preparedness and prevention, containing and limiting damages, restoration of activity, and learning) at OOREDOO Q.S.C. (Ooredoo), Qatar - Company, in addition to highlighting the role of strategic leadership in Crisis management in the Company. The study found that there is a statistically significant effect of Strategic leadership practices of all dimensions on Crisis management. It recommended that OOREDOO Q.S.C. (Ooredoo), Qatar - Company focus more on studying and analyzing its internal environment to identify the strengths and weaknesses in it and identify possible indicators of the occurrence of the crisis, and thus help it to enhance its strengths and take appropriate solutions to remedy its weaknesses, along with taking the necessary measures to prevent crises from occurring and reducing their impacts and its negative repercussions.